An optimized transversely isotropic, hyper-poro-viscoelastic finite element model of the meniscus to evaluate mechanical degradation following traumatic loading. Issue 8 (1st June 2015) - Wheatley, Benjamin B.; Fischenich, Kristine M.; Button, Keith D.; Haut, Roger C.; Haut Donahue, Tammy L.
Abstract: Inverse finite element (FE) analysis is an effective method to predict material behavior, evaluate mechanical properties, and study differences in biological tissue function. The meniscus plays a key role in load distribution within the knee joint and meniscal degradation is commonly associated with the onset of osteoarthritis. In the current study, a novel transversely isotropic hyper-poro-viscoelastic constitutive formulation was incorporated in a FE model to evaluate changes in meniscal material properties following tibiofemoral joint impact. A non-linear optimization scheme was used to fit the model output to indentation relaxation experimental data. This study is the first to investigate rate of relaxation in healthy versus impacted menisci. Stiffness was found to be decreased ( p =0.003), while the rate of tissue relaxation increased ( p =0.010) at twelve weeks post impact. Total amount of relaxation, however, did not change in the impacted tissue ( p =0.513).